Las excavaciones de Tel Abu Hawan en 1985-1986 y la cronología de la expansión fenicia hacia Occidente - Aznar, Carolina; Balensi, J.; Herrera, M. D. (Gerión. Revista de Historia Antigua, 2005)
The Stratum III of the excavations of R.W. Hamilton at the site of Tell Abu Hawam (Haifa, Israel) is important in chronological debates because of yielding Aegean pottery in the Levant and of having pottery parallels in materials of the first Phoenician colonies in the West. In a revision of Hamilton’s excavations (who dated it to 1000-925 (?) B.C.), Herrera dated it to ca. 1025/1000-750/725 B.C. and subdivided it into six phases. In this article we present the new dating, propose adjusting its end to ca. 759 B.C., and provide new data in the light of the excavations and paleoenvironmental studies of the Mission Archéologique de Tell Abu Hawam.